The relationship between quality of governance and foreign tourist numbers. - Professor R. Steyn; O. Jansen van Vuuren (African Journal of Hospitality, Tourism and Leisure, 2016)
Foreign tourists’ visits potentially constitute a valuable contributor to the gross domestic product and foreign currency reserves of the host country. Governments seemingly acknowledge this and often introduce specific programmes to attract foreign tourists. This research proposes that general good governance alone relates to the number of tourists to be expected and that countries with good governance attract larger numbers of tourists than those who display poor governance. A hypothesis was tested where six proxies of good governance were used to predict tourism numbers in 158 countries. The data revealed that four of these proxies predicted tourism numbers, declaring 18.7% of the variance in tourism numbers. This research is important as it shows that tourists are attracted to countries which show high levels of good governance. When programmes to attract tourists are designed, this type of information should be included. These results should, however, be interpreted with caution, as at the time of testing the model, predictions were not particularly accurate for some countries.